Mediation, new function of inspection from the LOMLOE. Some experiences in professional practice - Romero Ureña, Carmen (Avances en Supervisión Educativa, 2024)
The modification of the LOE by the LOMLOE has introduced a new function of educational inspection that, although it was already carried out by inspectors, is now reflected and, therefore, becomes relevant; It consists of guidance to management teams in the adoption and monitoring of measures that favor coexistence, the participation of the educational community and the resolution of conflicts, promoting and participating, when necessary, in mediation processes. That is why this article clarifies what these processes of orientation and direct participation can be, differentiating between mediation and arbitration and giving examples of direct action experienced in the daily work of an inspector.
Keywords: inspection; mediation; arbitration; coexistence; conflicts